A study of the efficacy of fathers’ attachment training on paternal-fetal attachment and parental anxiety - Setodeh, Sara; Pourahmad, Saeedeh; Akbarzadeh, Marzieh (Family Medicine & Primary Care Review, 2017)
Background . Attachment behaviors play an important role in accepting the identity of the fathers, the pleasant outcome of pregnancy and the child’s growth and development in the future. Objectives . This study aimed to investigate the effect of father’s attachment training (awaiting a child) on paternal-fetal attachment and parental anxiety. Material and methods . This clinical trial was conducted on 150 spouses of eligible pregnant women. In the intervention group, four 90-minute training sessions were designed on maternal-fetal attachment, while the control group received routine prenatal care. The questionnaire of paternal-fetal attachment was completed both before and after intervention in both cases and control groups. Data analysis was done in SPSS software using a paired t-test and independent t-test (the significant level was 0.05). Results . The mean score of attachment was reported as 56.61 ± 6.05 and 64.53 ± 6.94 both before and after intervention, respectively. According to the paired t-test, there was a significant difference in the attachment score after intervention (p < 0.001). According to the independent t-test applied a month after intervention, the comparison of fathers’ anxiety scores before and after intervention showed a significant difference between the control and intervention groups (p < 0.001). Conclusions . Training fathers about attachment skills leads to increased paternal-fetal attachment and a lower anxiety score. Therefore, it seems necessary to include education of fathers in prenatal care.